Learning History from Novel: A Case Study in Arabic Literature - Lesmana, Maman (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: In studying related to the aspects of historical novel, the literature experts classified all of the historical novel into three main categories, namely: propaganda, education, and escapism. This classification is not based on aesthetic considerations, but on the issue of historical truth. Accordingly, the first and third classifications mislead or ignore the historical truth, while the second classification abuses the novel media. Propaganda historical novels generally have political or religious motives, educational historical novels aims to provide factual information to the reader, and escapism historical novels are largely intended to provide entertainment. Meanwhile, other literature experts divided the historical novel into two categories, namely: traditional historical novels and post-modernist historical novels. The traditional historical novel reached its peak popularity in the 19th century, and is often used as material for study by the critics at the time. A general characteristic of this novel, which is also regarded as a weakness, is often to incorporate elements of romantic love in addition to elements of history. Meanwhile, post-modernistsâ historical novels reject such forms. Based on the classification, this article attempts to examine the historical novels in Arabic literature and how they are categorized. Historical novels which are used as the case studies in this article are the works of historical novels by Jurji Zaydan (1861), Naguib Mahfouz (1911), and Gamal al-Ghitani (1945).KEY WORDS: Historical novel, Arabic literature, category and classification, historical truth, the works of Jurji Zaydan, Naguib Mahfouz, and Gamal al-Ghitani.About the Author: Dr. Maman Lesmana is a Senior Lecturer at the Arabic Language Department, Faculty of Humanities UI (University of Indonesia), UI Campus Depok, West Java, Indonesia. For academic purposes, he can be contacted via e-mail at: malessutiasumarga@yahoo.comHow to cite this article? Lesmana, Maman. (2014). âLearning History from Novel: A Case Study in Arabic Literatureâ in TAWARIKH: International Journal for Historical Studies, Vol.6(1) October, pp.83-92. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (January 11, 2014); Revised (May 20, 2014); and Published (October 28, 2014).